2021
DOI: 10.3390/children8050402
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Computed Tomography Findings in Pulmonary Vein Stenosis

Abstract: (1) Pulmonary vein stenosis (PVS) can be a severe, progressive disease with lung involvement. We aimed to characterize findings by computed tomography (CT) and identify factors associated with death; (2) Veins and lung segments were classified into five locations: right upper, middle, and lower; and left upper and lower. Severity of vein stenosis (0–4 = no disease–atresia) and lung segments (0–3 = unaffected–severe) were scored. A PVS severity score (sum of all veins + 2 if bilateral disease; maximum = 22) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…[23] Additionally, it was shown that PVS severity correlated with the severity of the corresponding lung segment in PVS in children. [24]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Additionally, it was shown that PVS severity correlated with the severity of the corresponding lung segment in PVS in children. [24]…”
Section: Discussionmentioning
confidence: 99%
“…[23] Additionally, it was shown that PVS severity correlated with the severity of the corresponding lung segment in PVS in children. [24] Either over-or underinflation of the balloon or stent may affect restenosis, which has been demonstrated in coronary artery intervention. [25][26][27] Earlier studies documented some factors of restenosis after percutaneous coronary intervention, including vessel size, maximal balloon pressure, stent type, final diameter stenosis, DM, etc.…”
Section: In-stent Restenosis and Associated Factors In Pv Interventio...mentioning
confidence: 99%
“…Common manifestations of PVS due to multiple diseases on CT are parenchymal changes (eg, consolidation, "ground glass" opacities, interlobular septal thickening, and volume loss). [33,79,93] Pulmonary vascular changes (eg, oligemia, slowed flow, and collaterals) are also present in patients with PVS. [93] Typical FM dyad/triad/tetralogy is also observed in patients with FM-PVS.…”
Section: Chest Ct and Ctpvmentioning
confidence: 99%
“…Its severity depends on the number of affected vessels, stenosis site and degree, and comorbidities. [2,79] Single or mild PVS is always asymptomatic during its early stage. In contrast, exertional dyspnea, hemoptysis, PH, and RHF are common in the late PVS stage or severe cases.…”
Section: Clinical Presentation Of Pvsmentioning
confidence: 99%
“…33 Further, CTA allows for the application of a scoring system of PVS severity that has been demonstrated to correlate well with lung disease severity and with PVS-related mortality. 34,35 Cardiac magnetic resonance imaging Cardiac magnetic resonance (CMR) imaging is less commonly employed as a screening or surveillance tool in the management of PVS. It is limited by the duration of the examination, the need for sedation, artifact from previous stent implantation as well as the limited spatial resolution it provides, particularly in smaller patients.…”
Section: Nuclear Medicine Lp Scanmentioning
confidence: 99%